Budidaya Ikan Cupang (Betta Splendens) Menggunakan Wadah Sederhana Di Desa Pangkalan Serik - Sila Pandu Pamungkas; Muhammad Jaya Adi Putra; Siti Nurhalizah; Dira Damayanti; Anggita Putri Mulyani; Nurhusna Nurhusna; Siti Safrida; Debby Lestari; Muhammad Alifil Kirom; Rofifah Zakiyah; Mega Fajarina (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2022)
This service aims to provide good and correct maintenance training for betta fish (Betta sp.) in accordance with the SNI for ornamental betta fish to the community of Pangkalan Serik Village, Siak Hulu District, Kampar Regency. Lack of public understanding about betta fish cultivation and the potential in terms of economy there is no betta fish cultivator in Pangkalan Serik. The solution offered from this service is to provide additional skills to the community in Pangkalan Serik, Siak Hulu for good and correct maintenance of betta fish in accordance with the SNI for ornamental betta fish. The service method is a discussion and direct practice on how to cultivate good and correct betta fish (Betta sp.). Implementation of community service activities through discussions and socialization of ornamental betta fish (Betta sp.) which can increase people's income. The results obtained from the service are that the community is very enthusiastic about cultivating ornamental betta fish (Betta sp.) and hopes that the program so that this community service can continue to be carried out to provide assistance to the community.